2012
DOI: 10.2320/matertrans.m2011256
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chlorine to Remove Magnesium from Molten Aluminum

Abstract: Removal of Mg from aluminum scraps, known as demagging, has been widely applied in the aluminum industry. This work discusses bubble-formation theories and magnesium kinetic removal from aluminum scraps using chlorine and inert gas fluxing. The interfacial area of the bubbles and residence time were estimated using a mathematical model. To inject gaseous chlorine, three types of nozzles were used with varying internal diameter. In addition, a porous plug, as well as varying input chlorine flow and concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Fig.6a is an experimental result obtained by Vieira et al [17]. Argon gas was purged into the aluminium melt at various velocities and it was found that the oxide layer on the surface prevents the melt from further oxidation.…”
Section: Removal Of Magnesiummentioning
confidence: 85%
See 2 more Smart Citations
“…Fig.6a is an experimental result obtained by Vieira et al [17]. Argon gas was purged into the aluminium melt at various velocities and it was found that the oxide layer on the surface prevents the melt from further oxidation.…”
Section: Removal Of Magnesiummentioning
confidence: 85%
“…Application of chlorine not only reduces the magnesium content in the melt but also assists the removal of alkali metals, alkali earth metals, hydrogen. In addition to that, phase separation between the liquid metal and solid inclusions is also achieved [13], [17].…”
Section: Removal Of Magnesiummentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the alloy is produced from scrap, the resultant Mg content of the alloy is higher than 0.1 wt-% and the excess of Mg needs to be removed. Vieira et al [5] used the chlorine method and discuss bubble-formation theories and magnesium kinetic removal from aluminum scraps using chlorine and inert gas fluxing. In spite of that Neff and Cochran [6] showed that the kinetics of the magnesium removal as MgCl 2 is rapid, but the unreacted chlorine and the gaseous coproduct AlCl 3 can limit the environmental acceptability of the process.…”
Section: Introductionmentioning
confidence: 99%